Noroviiruse tüved Eestis 2015–2016 ägeda gastroenteriidiga hospitaliseeritud lastel vanuses 0–18 aastat - Kõivumägi, Kadri; Geller, Julia; Toompere, Karolin; Soeorg, Hiie; Kallas, Eveli; Jõgeda, Ene-Ly; Huik, Kristi; Lutsar, Irja (Eesti Arst, 2022)
Eesti Arst 2022; 101(9):509